Decay and stability of solutions to the Fokker–Planck–Boltzmann equation in. Issue 11 (18th August 2018) - Wang, Xiaolong; Shi, Huangping
Abstract: In this paper, we use the method of constructing the compensating function introduced by Kawashima and the standard energy method to study the global existence of solutions to the Fokker–Planck–Boltzmann equation in the whole space. The time decay and uniform stability of solutions to the global Maxwellian are also obtained.